Acute Disseminated Toxoplasmosis in Two Specimens of Macropus rufogriseus Caused by a Genotype so far Exclusive to South America - Valenzuela-Moreno, Luis Fernando; Carmona-Muciño, María del Carmen; Cedillo-Peláez, Carlos; Rico-Torres, Claudia Patricia; Luna-Pastén, Héctor; Hernández-Rodríguez, María Alejandra; Caballero-Ortega, Heriberto (Frontiers in Veterinary Science, 2022)
Macropods are included among the species considered highly susceptible to Toxoplasma gondii infection. Clinically, it is difficult to distinguish between acute toxoplasmosis due to primary infection and reactivation of chronic latent infection in susceptible species until pathologic studies are performed. Here, we described the clinical cases and lesions found in two deceased Bennett’s wallabies (Macropus rufogriseus) with a presumptive diagnosis of toxoplasmosis, as well as the genetic characterization of the T. gondii isolates obtained from these specimens. Both animals presented acute infection lesions in the lungs, liver, spleen and lymph nodes associated to T. gondii infection. Histopathology and immunohistochemistry also demonstrated tissue cysts of different sizes, indicating that the wallabies were previously infected with this parasite. In addition, the parasitic load was calculated. Two isolates were obtained, one from each specimen and the molecular characterization was done; both isolates were the ToxoDB #116 genotype. This is the first study that reports the isolation of this particular genotype outside South America, and given the histopathological findings, it could be considered virulent for this species. The dynamics of infection that T. gondii is causing in definitive and intermediate hosts in a region allows us to know the risks to which the animals and humans that live in the area are exposed, and in the future to implement a preventive medicine plan against this parasite.